Acute physiological responses of blood flow restriction between high-intensity interval repetitions in trained cyclists - Pugh, C. F.; Paton, C. D.; Ferguson, R. A.; Driller, M. W.; Beaven, C. M. (European Journal of Sport Science, 2024)
Blood flow restriction (BFR) is increasingly being used to enhance aerobic performance in endurance athletes. This study examined physiological responses to BFR applied in recovery phases within a high-intensity interval training (HIIT) session in trained cyclists. Eleven competitive road cyclists (mean ± SD, age: 28 ± 7 years, body mass: 69 ± 6 kg, peak oxygen uptake: 65 ± 9 mL · kg-1 · min-1) completed two randomised crossover conditions: HIIT with (BFR) and without (CON) BFR applied during recovery phases. HIIT consisted of six 30-s cycling bouts at an intensity equivalent to 85% of maximal 30-s power (523 ± 93 W), interspersed with 4.5-min recovery. BFR (200 mmHg, 12 cm cuff width) was applied for 2-min in the early recovery phase between each interval. Pulmonary gas exchange (VO2, VCO2, and VE), tissue oxygen saturation index (TSI), heart rate (HR), and serum vascular endothelial growth factor concentration (VEGF) were measured. Compared to CON, BFR increased VCO2 and V?E during work bouts (both p < 0.05, dz < 0.5), but there was no effect on VO2, TSI, or HR (p > 0.05). In early recovery, BFR decreased TSI, VO2, VCO2, and V?E (all p < 0.05, dz > 0.8) versus CON, with no change in HR (p > 0.05). In late recovery, when BFR was released, VO2, V?CO2, V?E, and HR increased, but TSI decreased versus CON (all p < 0.05, dz > 0.8). There was a greater increase in VEGF at 3-h post-exercise in BFR compared to CON (p < 0.05, dz > 0.8). Incorporating BFR into HIIT recovery phases altered physiological responses compared to exercise alone.